513 Surgical Complications Following Reversal of Ileostomy. (19th August 2022) - Elzaafarany, A; Nordin, MN; Skervin, A; Grabham, J
Abstract: Aim: To identify the rate of patients who develop complications of Grade 3b or above according to Clavien-Dindo classification following reversal of ileostomies within 30 days from time of the operation. Method: This is a retrospective observation study of a single cohort. 147 patients who underwent reversal of Ileostomy following Anterior Resection of Rectal cancer, over a period of three years, were involved in the study. The primary outcome is the 30 days adverse events rate of grade 3b or above of Clavien-Dindo classification following reversal of ileostomies. Secondary outcome is identifying risk factors for developing these complications: age, gender, ASA, comorbidities, BMI, pre-operative haemoglobin, interval between primary surgery and reversal of ileostomy, duration of operation, type of anastomosis, surgical experience. Results: Out of 147 patients who underwent Reversal of Ileostomy, eight patients developed complications of Grade 3b or above. Five cases involved anastomotic leak requiring resection of anastomosis and ileostomy formation. One patient had an abdominal wall haematoma requiring evacuation of haematoma in theatre. One patient had a bleeding from anastomosis, required laparotomy and resection of anastomosis. One patient developed aspiration pneumonia followed by respiratory distress, multi-organ failure and died. Conclusions: The rate of patients who develop complications of Grade 3b or above following reversal of ileostomies within 30 days from the time of the operation, in our centre is low and is comparable to published literatures. Methods to minimise these complications should be further evaluated including proper pre-assessment of these patients in outpatient clinic to identify those of high risk for surgery.